Acute Femoropopliteal Bypass Graft Occlusion After Knee Manipulation Under Anesthesia: A Case Report and Review of Current Literature. (2nd February 2022) - Fulton, Zachary W.; Singleton, Amy; Davis, Kirk R.
Abstract : Bilateral tibiofemoral knee dislocations are a relatively rare injury, and there is a scarcity of literature on its appropriate evaluation and treatment. Even less knee dislocations with concomitant popliteal artery injury have been described. Postoperative graft occlusion accounts for approximately half of the overall complication rate, occurring in up to 18% of the patients undergoing femoropopliteal bypass grafting. Furthermore, anticoagulation and antiplatelet therapy after graft placement is a point of contention. Here, we describe a case of a knee dislocation with associated popliteal artery transection treated initially with successful knee-spanning external fixation and arterial grafting, respectively. At 6 weeks after injury, the patient underwent external fixation removal and closed manipulation of the knee for arthrofibrosis. After manipulation, yet still under anesthesia, distal pulses were acutely diminished and subsequent CTA demonstrated femoropopliteal graft thrombosis. This case demonstrates successful recognition, thrombectomy, and restoration of arterial blood flow, which has since been maintained. Written consent by the patient involved in this case report was obtained.